The Effects of Gradual Increasing of Financial Leverage, Measure of Free Cash Flow and Company’s Growth on Earnings Management of Companies Listed in Tehran Stock Exchange - Seyyed Abbas Hashemi (Shahid Bahonar University of Kerman, 2012)
The aim of this study is to investigate the effect of gradual increasing of financial leverage, measure of free cash flow, and company’s growth as the proxies of opportunistic behaviors of managers on earnings management. In this research, three hypotheses were developed and for their validation, samples were selected among the listed companies on Tehran Stock Exchange. Research period was the years 1999 to 2007, which was divided to five three-year periods. Afterwards, the eligible companies according to their level of financial leverage changes were classified into two control and test groups. The test and control groups include the companies with an increasing financial leverage and those with a high and constant financial leverage during the research period, respectively. The research results show that there is no significant difference for the rate of earning management between companies with a constant financial leverage and those with a gradual increasing financial leverage. The further results show the effects of free cash flows and company growth on managers’ opportunistic behaviors which can be impressive on rate of earnings management.